ANALISIS LATIHAN MENEMBAK BOLA KEARAH GAWANG DENGAN MENGGUNAKAN PUNGGUNG KAKI PADA PERMAINAN SEPAK BOLA PADA CLUB LAPPA UNITED - M Adam Mappaompo; Juhanis Juhanis; Hamka Hamka; Arifuddin Usman; Muhammad Salahuddin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
The problem in this research is that the Lappa United Sinjai Club in shooting at the goal is less accurate in football games . This research is an experimental research which aims to determine the effect of shooting the ball towards the goal using the back of the foot in the Lappa United Sinjai club soccer game. The population in this study were all 30 Lappa United Sinjai players, while the research sample consisted of 30 players. with sampling using total sampling. The ball shooting test is used as a data collection method. By using computer resources and the SPSS program version 21.00, descriptive statistics and inference t-test were the data analysis techniques performed. Based on the analysis of the data and the findings of this study, it can be said that training with the instep has a major impact on increasing the practice of shooting the ball towards the goal in soccer games at Club Lappa United Sinjai